Profile of Students’ Mathematical Creative Thinking Ability in Solving Open-Ended Problems - Wina Wina; Neneng Tita Rosita; Lia Yuliawati (MASI Mandiri Edukasi, 2026)
This study aimed to describe the profile of students’ mathematical creative thinking skills in solving open-ended problems on data presentation. Mathematical creative thinking was analysed based on four creativity indicators proposed by Torrance: fluency, flexibility, originality, and elaboration. The research employed a descriptive qualitative approach and was conducted at SMP Negeri 2 Pamulihan. The research subjects consisted of 32 seventh-grade students selected through purposive sampling to represent four categories of creative thinking ability: highly creative, creative, moderately creative, and less creative. Data were collected using a mathematical creative thinking skills test, task-based interviews, and observations of students’ problem-solving processes. Data analysis was conducted through data reduction, data display, and conclusion drawing, supported by the triangulation of techniques and data sources to ensure validity. The results indicated that students’ mathematical creative thinking skills varied across categories. Students in the highly creative category achieved an overall score of 34.375% across all creativity indicators, demonstrating the ability to generate diverse ideas, apply multiple problem-solving strategies, produce original solutions, and present detailed and systematic explanations. Students in the creative category achieved the highest percentage, 37.5%, showing strong performance particularly in fluency and flexibility, although originality and elaboration were not consistently demonstrated. Students in the moderately creative category obtained a score of 9.375%, indicating limited creative thinking skills that were mostly confined to fundamental indicators, with minimal originality and elaboration. Meanwhile, students in the less creative category achieved 18.75%, characterised by reliance on a single strategy and brief, superficial explanations.